Agrobacterium Tumefaciens-Mediated Transformation Of Cabbage (Brassica Oleracea Subsp. Capitata) Cv. Ky Cross With Athsp101 Gene - Rafat, Arash (2008)

(untitled)
An Agrobacterium tumefaciens-mediated transformation was developed for cabbage (Brassica oleracea subsp. capitata) cultivar KY Cross by introduction of the AtHSP101 gene. The AtHSP101 cDNA was cloned in place of gusA in pCAMBIA1301 binary vector to produce an effective binary vector construct of AtHSP101 gene for transformation work. The construct named pCAMHSP and the successful cloning was confirmed by both restriction enzymes analysis and Polymerase Chain Reaction (PCR) assay. Electrophoresis of double digestion product of pCAMHSP binary vector (~12.5Kb) showed both the expected band sizes of ~9800 bp and ~2750 bp. Also, PCR analysis produced a ~2750 bp band which indicated the presence of the AtHSP101 inside the pCAMHSP designed binary vector. Before transformation, the minimum inhibitory concentration of hygromycin was determined for hypocotyl and shoot tip explants of cabbage cv. KY Cross to be used in the selection of putative transformants. Hygromycin B at 3.5 and 10 mg/L were selected as the minimum inhibitory concentrations for causing the death of hypocotyl and shoot tip explants respectively. Two different Agrobacterium tumefaciens strains (C58 and GV2260) were co-cultivated with the two types of explants (hypocotyl and shoot tip) to optimize factors that could contribute to the improvement of the Agrobacterium tumefaciens-mediated transformation of cabbage cv. KY Cross. The effect of preculture and acetosyringone on improvement of transformation frequency was determined by using three preculture treatments (without preculturing, preculturing on Callus Inducing Medium, and preculturing on Shoot Regeneration Medium) in combination with two different acetosyringone concentrations (0 and 100 μM)). The duration of three days preculture on the Callus Induction Medium in combination with 100 μM acetosyringone applied in the Agrobacterium culture medium resulted the highest percentage of transformation from hypocotyl explants (15% and 30% using A. tumefaciens strain C58 and GV2260 respectively). Meanwhile, the highest percentages of transformation from shoot tip explants (12.5% and 17.5% using A. tumefaciens strain C58 and GV2260 respectively) were observed by the application of 100 μM acetosyringone in the Agrobacterium culture medium but without preculturing. The effect of bacterial dilution and inoculation time on improvement of transformation frequency was also determined. Three different bacterial dilution rates (1:5, 1:10, and 1:15) and three different inoculation times (5, 10, and 20 min) were assessed. It was found that 1:10 Agrobacterial dilution and 5 minutes inoculation period resulted in the highest transformation frequency in both hypocotyl (20% and 35% using A. tumefaciens C58 and GV2260 respectively) and shoot tip explants (15% and 17.5% using A. tumefaciens C58 and GV2260 respectively). A shoot induction system after cocultivation was established. Multiple shoot formation from hypocotyls and shoot tip explants of cabbage ( Brassica olarecea subsp. capitata) cultivar KY Cross was evaluated after cocultivation on MS medium containing 500 mg/L carbenicillin and different concentrations of BAP (0, 1, 2, 3 and 5 mg/L). The highest percentage of shoot formation and mean number of shoots for both hypocotyl (87.5% and 90% using A. tumefaciens C58 and GV2260 respectively) and shoot tip explants (92.5% and 95% using A. tumefaciens C58 and GV2260 respectively) were obtained on 2 mg/L BAP. The highest mean number of shoots for both hypocotyl (5.60 using both A. tumefaciens C58 and GV2260) and shoot tip explants (3.0 and 3.17 using A. tumefaciens C58 and GV2260 respectively) were also obtained on 2 mg/L BAP. Confirmation of the transformed lines was determined by PCR using primers of AtHSP101 gene. Observation of the expected sized fragment of 196 bp in some putative transformant lines confirmed the integration of AtHSP101 gene into the transformed plants genome. The highest percentages of transformation from hypocotyl and shoot tip explants were 45% and 32.5% respectively.